Neutrophil death induced by a triathlon competition in elite athletes - Levada-Pires, A. C.; Cury-Boaventura, M. F.; Gorjao, R.; Hirabara, S. M.; Puggina, E. F.; Peres, C. M.; Lambertucci, R. H.; Curi, R.; Pithon-Curi, T. C. (Medicine & Science in Sports & Exercise, 2008)
Abstract: Introduction/Purpose: The effect of a triathlon competition on death of neutrophils from elite athletes was investigated.